2009
DOI: 10.1080/00927870902861356
|View full text |Cite
|
Sign up to set email alerts
|

FP-Injective Complexes

Abstract: In this article, FP-injective complexes are introduced and studied. We prove that ( ⊥ is a hereditary cotorsion theory if and only if R is a left coherent ring, where denotes the class of all FP-injective complexes of left R-modules. Simultaneously, we study the existence of FP-injective preenvelopes and FP-injective covers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…As one of important abelian categories, the category of complexes of modules has been studied by many authors (see, for example [1,4,13,10,11,17,25]), and many results of the category of modules which have been generalized to the category of complexes of modules. As we know, injective and flat complexes play important roles in the study of the category of complexes of modules, and a complex C is injective (resp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of important abelian categories, the category of complexes of modules has been studied by many authors (see, for example [1,4,13,10,11,17,25]), and many results of the category of modules which have been generalized to the category of complexes of modules. As we know, injective and flat complexes play important roles in the study of the category of complexes of modules, and a complex C is injective (resp.…”
Section: Introductionmentioning
confidence: 99%
“…flat) if and only if C is exact and Z m (C) is injective (resp. flat) as R-modules for any m ∈ Z; In [25,23], Liu et al introduced the notion of FP-injective complexes, they obtained many nice characterizations of them over coherent rings, and they showed that some properties of injective complexes have counterparts for FP-injective complexes. More recently, we introduced and investigated in [16,14] weak injective and weak flat modules, and generalized many results from coherent rings to arbitrary rings.…”
Section: Introductionmentioning
confidence: 99%